Answer:
x = 3
or

Explanation:
3x² - 5x - 12 = 0
Method 1: Factoring
3x² + 4x - 9x - 12 = 0
(3x² + 4x) + (- 9x - 12) = 0
x(3x + 4) - 3(3x + 4) = 0
(x - 3)(3x + 4) = 0
Two separate equations
x - 3 = 0
3x + 4 = 0
x - 3 = 0
x - 3 + 3 = 0 + 3
3x + 4 = 0
3x + 4 - 4 = 0 - 4
3x = - 4


Method 2: Quadratic Formula
Ignore the A before the ±, it wouldn't let me type it correctly.

3x² - 5x - 12 = 0
a = 3
b = - 5
c = - 12






Two separate equations
One must have a + (positive) and the other will have a - (negative).


x = 18 ÷ 6
x = 3


x = - 8 ÷ 6
